Recently employed engineering techniques to reduce the spread of COVID-19 (corona virus disease 2019): a review study - Bander Saman; Mahmoud M. A. Eid; Marwa M. Eid (Institute of Advanced Engineering and Science, 2021)
The main challenges of today’s global health care system are to reach to strong healthcare system, to provide effective methods to eliminate the increase in the number of dead and infected with virus of COVID-19. Therefore, during the last few months, the great importance and efficacy of a variety of engineering techniques that have greatly contributed in curbing the spread of the COVID-19, and evenly help to eliminate it according to recent scientific studies was highly prominent. Among these promising technologies in this field we mention, but not limited to, the use of ultraviolet (UV) rays to disinfection of air and surfaces. In addition, thermal imaging technology, which was employed using infrared radiation for monitoring people in crowded areas and human groups to determine who have abnormal temperatures, so that all preventive measures are taken. Robots have also been used and harnessed to perform many tasks that limit the spread of the virus and maintain the integrity of the human element. Last but not least, facial recognition techniques have also been used to limit the spread of this pandemic. Ultraviolet radiation is one of physical therapy modalities that can be used to increase the efficiency of human immune system to fight the virus. In conclusion UV radiation, infrared thermal imaging, robotics, AFR technologies are now widely used to reduce the spread of this virus and manage the outbreak.